The prospect of using modified local starches from cocoyam and wheat starches as fluid loss material in a water - based drilling (2017)
As an oil producing nation, Nigeria embarks on substantial drilling activities. The additives used for these activities are all imported as a result there is need to reduce the over dependency on foreign additives this has necessitated the sourcing locally for suitable substitute. During drilling, adequate filtration control is essential to prevent drilling problems such as excessive torque and drag; differential pressure sticking; borehole instability; and formation damage. This study was aimed at a comparative analysis of the use of wheat starch and cocoyam chemically modified with ammonium phosphate and sodium acetate as suitable fluid loss additives in a water-based mud. The filtration properties of a water- base fluid formulated with variable quantities of the chemically modified starch were determined using the recommended standard API practice at different conditions of temperatures with Carboxymethylated Cellulose CMC used as control. Using Eviews 7, the statistical analysis showed drilling fluid formulated with starches treated with sodium acetate had a fluid loss value in the range of 4.0 - 8.9 mls, while those from starches modified with ammonium phosphate had a fluid loss of 4.3 - 8.3 mls; although, these values were lower than 9.1 - 11.1 mls for CMC formulated mud, the results show that mud sample treated with modified wheat starch and cocoyam starch can significantly reduce fluid loss in a water based drilling mud, thereby confirmed that polymer can be used as fluid loss control agent in the mud system